Goal orientation and sensation seeking in relation to optimal mood states among skateboarders - Boyd, M. P.; Kim, M.-S. (Journal of Sport Behavior, 2007)
The purpose of this study was to examine the multivariate relationship between both goal orientations and sensation seeking in sport, and psychological mood states among a sample of skateboarders. Male skateboarders (N=68), ages 18-28, voluntarily provided informed consent, and subsequently completed several response measures, anonymously, at one of two landmarks in an urban area where skateboarders were known to congregate for practice and informal competition. The results of canonical correlation indicated a significant and meaningful relationship between the canonical variates consisting of goal orientations/sensation seeking and psychological mood states. In order of magnitude, positive loadings on task orientation (.856) and sensation seeking (.599) corresponded positively with the mood state of vigor-activity (.871), and negatively with the mood states of tensionanxiety (-.469) and anger-hostility (-.374), F (15, 166) = 1.91, p< .025. Ego orientation, however, failed to contribute any significant variance to the multivariate relationship. Discussion highlights the potential beneficial nature of both a task orientation and sensation seeking in sport with respect to optimal psychological mood states among a sample of skateboarders.